Variant selection mechanism by elastic anisotropy and double K-S relation for transformation texture in steel; difference between martensite and ferrite. (March 2018) - Tomida, Toshiro
Abstract: Variant selection mechanisms in the phase transformation in steels have been investigated experimentally as well as theoretically. The characteristics of transformation textures from the deformed austenite in 0.1%C-1.1%Mn hot-rolled steel are the development of components lying in the range from {211}<011> to {332}<113>, and the {332}<113> component further evolves by displacive martensite transformation than by diffusive ferrite transformation. Via transformation texture calculation based on the observed textures, various mechanisms of variant selection have been explored particularly for martensite transformation. Whereas all the conventional models examined have failed to quantitatively reproduce the experimental textures of martensite, the mechanism based on the elastic anisotropy in neighboring matrices and the dual orientation relation to two parent grains (Double K-S relation) have successfully reproduced the experimental texture of martensite and the characteristic texture difference between martensite and ferrite at a hitherto unattainable level. The phenomenon of so-called variant pairing in low carbon lath martensite can also be explained by the elastic anisotropy mechanism. Graphical abstract: Image 1